Tongue Twister Method in Teaching Pronunciation: A Narrative Inquiry of Pre-Service English Teacher - Nadia Puspita; Kelik Wachyudi; Nia Hoerniasih (Edukasiana: Jurnal Inovasi Pendidikan, 2023)
Since English has become a foreign language in Indonesia, the capability to communicate in English has become ever more crucial. Correct speech is progressively required to prevent misunderstandings in articulating a message to the public. As a result, teaching English speaking is essential for teachers to improve their students' speaking abilities. As English is a second language in Indonesia, students struggle to acquire it. In the context of communication, the mother tongue or the language used in daily activities is more dominant. Because the use of foreign languages is still descending, one of the alternative techniques that a teacher can accomplish is a tongue twister. Tongue twisters as a teaching method enable pupils to speak more clearly, especially when pronouncing words. This research aims to report on the researchers’ experience using tongue twister to teach pronunciation in speaking practice. This research was conducted in an Indonesian Vocational High School in the Karawang district. Besides that, the role of the researchers was as active observers. The findings are that students relish learning using the tongue twister technique. Relish means that the students vigorously participate in learning because the teaching method is delightful and comfortable for students to comprehend the crux material. Therefore, the tongue twister technique assists students in learning English speaking continually.